What do young people with rheumatic conditions in the UK think about research involvement? A qualitative study - Suzanne Parsons (Pediatric Rheumatology Online Journal, 2018)
Abstract Background Involving people of all ages in health research is now widely advocated. To date, no studies have explored whether and how young people with chronic rheumatic conditions want to be involved in influencing health research. This study aimed to explore amongst young people with rheumatic conditions, 1) their experiences of research participation and involvement 2) their beliefs about research involvement and 3) beliefs about how young people’s involvement should be organized in the future. Methods Focus groups discussions with young people aged 11–24 years with rheumatic conditions across the UK. Data was analysed using a qualitative Framework approach. Results Thirteen focus groups were held involving 63 participants (45 F: 18 M, mean age 16, range 10 to 24 years) across the UK. All believed that young people had a right to be involved in influencing research and to be consulted by researchers. However, experience of research involvement varied greatly. For many, the current project was the first time they had been involved. Amongst those with experience of research involvement, awareness of what they had been involved in and why was often low. Those who had previously participated in research appeared more positive and confident about influencing research in the future. However, all felt that there were limited opportunities for them to be both research participants and to get involved in research as public contributors. Conclusions These findings suggest that there is an on-going need to both increase awareness of research involvement and participation of young people in rheumatology as well as amongst young people themselves.